Composite hydrogel, composite aerogel, preparation method and application

The preparation of composite hydrogels and composite aerogels by high-energy irradiation method has solved the problem that graphene-based aerogels are prone to blockage or poor moisture transmission capabilities in the field of solar photothermal water evaporation, and achieved the ability of not easily blockage and moisture transmission capabilities. Excellent effect improves solar-thermal energy conversion efficiency.

CN119391005APending Publication Date: 2025-02-07SHANGHAI INSTITUTE OF APPLIED PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411516790.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Graphene-based aerogels are prone to block evaporators or poor moisture transmission capabilities in the field of solar photothermal water evaporation.

Method used

Compound hydrogels and composite aerogels are prepared by high-energy irradiation method. Mixed liquid A includes graphene oxide, inorganic nanomaterials, acrylic acid and its derivatives monomers, water and alcohol-based water-soluble compounds, by adjusting components The proportion and irradiation conditions form materials that are not easy to block and have excellent moisture transfer capabilities.

Benefits of technology

It has achieved the effect of not easily blocking the evaporator in the field of solar photothermal water evaporation and excellent moisture transmission capacity, improved the solar-heat energy conversion efficiency, and has a wide application value of seawater desalination and wastewater purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391005A_ABST
    Figure CN119391005A_ABST
Patent Text Reader

Abstract

The invention discloses a composite hydrogel, a composite aerogel, a preparation method and an application. The preparation method of the composite hydrogel comprises the following steps: irradiating a mixed solution A with high-energy rays; wherein the mixed solution A comprises graphene oxide, an inorganic nano material, monomers of acrylic acid and derivatives thereof, water and an alcohol water-soluble compound; the inorganic nano material is selected from one or more of an MXene two-dimensional lamellar material, a metal oxide and a metal sulfide; in the mixed solution A, the content of the graphene oxide is 0.05-10 mg / mL, the mass ratio of the graphene oxide to monomers of acrylic acid and derivatives thereof is 1: (50-1000), and the mass ratio of the graphene oxide to the inorganic nano-material is 1: (0.1-100); the alcohol water-soluble compound accounts for 2-50% of the mixed solution A in percentage by mass. When the composite hydrogel and the composite aerogel are applied to the field of solar photo-thermal water evaporation, an evaporator is not prone to being blocked.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite hydrogel, a composite aerogel, a preparation method and an application thereof. Background Art

[0002] Freshwater resources are increasingly scarce. At present, seawater desalination and wastewater purification are the main ways to obtain fresh water. In industrial production, they mainly include traditional methods such as distillation and membrane separation. However, these technologies have disadvantages and shortcomings such as high cost, high energy consumption and easy membrane pollution. In recent years, the application of solar energy in seawater desalination and wastewater purification as a clean and sustainable energy has attracted widespread attention. An efficient solar evaporator is based on excellent photothermal conversion materials and a continuous water supply. Among them, photothermal materials mainly include metal nanoparticles, semiconductor nanoparticles, near-infrared, organic and carbon-based materials. Graphene is a carbon-based two-dimensional sheet material with high mechanical strength, surface area, thermal conductivity and electrical conductivity. It has great application prospects in energy storage and conversion, catalysts, sensors and environmental protection. Compared with metal nanoparticles and semiconductor nanoparticles, graphene as a photothermal material has the advantages of low cost, high content and low weight. At the same time, due to its extensive π-π conjugated system and layered structure, graphene exhibits excellent light absorption and high solar heating efficiency in the 200-2500nm spectral range.

[0003] Although graphene has excellent photothermal evaporation capabilities, when applied to evaporators, actual evaporators often evaporate seawater in complex water systems. Organic pollutants in seawater can easily clog the evaporator, greatly reducing the evaporation efficiency of the evaporator. The introduction of inorganic nanomaterials can enhance photocatalytic capabilities, which can theoretically solve this problem well.

[0004] However, when graphene and inorganic nanomaterials are used as photothermal materials, the water transmission channel is unstable. Some studies have used cotton or non-woven fabrics as water supply devices for solar heating evaporators. However, this method has some disadvantages and shortcomings, such as the water supply rate is lower than the heating evaporation rate, severe heat loss, and salt accumulation.

[0005] In the preparation process of graphene-based gel, the amount of each component, the structure and dimensional stability of the raw material compounds will affect the performance of the final product.

[0006] Therefore, there is an urgent need to provide a graphene-based gel that is not easy to clog the evaporator and has excellent water transmission capacity when used in the field of solar thermal water evaporation. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the defects of the prior art graphene-based aerogels that are easy to clog the evaporator or have poor water transmission capacity when applied to the field of solar thermal water evaporation, and provide a composite hydrogel, a composite aerogel, and a preparation method and application. The composite hydrogel and composite aerogel of the present invention are not easy to clog the evaporator when applied to the field of solar thermal water evaporation and have excellent water transmission capacity.

[0008] The present invention solves the above technical problems through the following technical solutions.

[0009] The present invention provides a method for preparing a composite hydrogel, which comprises the following steps:

[0010] High-energy rays irradiate mixed solution A; wherein the mixed solution A comprises graphene oxide, inorganic nanomaterials, monomers of acrylic acid and its derivatives, water and alcohol-type water-soluble compounds; the inorganic nanomaterials are selected from one or more of MXene two-dimensional sheet materials, metal oxides and metal sulfides;

[0011] In the mixed solution A, the content of the graphene oxide is 0.05-10 mg / mL, the mass ratio of the graphene oxide to the monomers of acrylic acid and its derivatives is 1:(50-1000), and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:(0.1-100); the mass percentage of the alcohol water-soluble compound in the mixed solution A is 2-50%.

[0012] In the present invention, preferably, the high-energy rays are cobalt-60 gamma rays or electron beam rays.

[0013] In the present invention, the irradiation is performed in, for example, an irradiation reactor, and the irradiation reactor is, for example, a cylindrical irradiation reactor.

[0014] In the present invention, preferably, during the irradiation process, the absorbed dose rate of the high energy rays is 0.1-10 kGy / h, for example, 2 kGy / h, 5 kGy / h or 6 kGy / h.

[0015] In the present invention, during the irradiation process, the absorbed dose of the high-energy rays is generally 20-500 kGy, preferably 20-400 kGy, more preferably 30-300 kGy, further more preferably 50-200 kGy, for example 30 kGy, 80 kGy, 100 kGy, 150 kGy or 300 kGy.

[0016] In the present invention, preferably, before the mixed liquid A is irradiated with high-energy rays, nitrogen and / or argon are introduced into the mixed liquid A to remove oxygen in the mixed liquid A.

[0017] In the present invention, preferably, the mixed solution A is free of oxygen or has an oxygen concentration lower than 5%.

[0018] In the present invention, preferably, the size of the graphene oxide is nanoscale graphene oxide.

[0019] In the present invention, preferably, when preparing the mixed solution A, the graphene oxide is first prepared as a graphene oxide dispersion liquid. Wherein, the solvent of the graphene oxide dispersion liquid is preferably water.

[0020] The graphene oxide dispersion can be prepared by conventional methods in the art. Preferably, the graphene oxide dispersion is prepared by an oxidative exfoliation graphite method (i.e., the Hummers method).

[0021] In the present invention, preferably, the monomers of acrylic acid and its derivatives are selected from one or more of acrylamide, acrylic acid, methacrylic acid, and N,N-dimethylacrylamide, such as acrylamide.

[0022] In the present invention, preferably, the alcohol water-soluble compound is selected from one or more of monohydric alcohols having 1 to 4 carbon atoms, dihydric alcohols having 2 to 8 carbon atoms, trihydric alcohols having 3 to 4 carbon atoms, and polyhydric alcohols.

[0023] Preferably, the monohydric alcohol having 1 to 4 carbon atoms is selected from one or more of a primary monohydric alcohol, a secondary monohydric alcohol and a tertiary monohydric alcohol.

[0024] More preferably, the monohydric primary alcohol is selected from one or more of methanol, ethanol, n-propanol and n-butanol, for example, ethanol.

[0025] More preferably, the monohydric secondary alcohol is isopropanol and / or isobutanol, for example isopropanol.

[0026] More preferably, the monohydric tertiary alcohol is tert-butyl alcohol.

[0027] Preferably, the diol having 2-8 carbon atoms is selected from one or more of ethylene glycol, propylene glycol and octanediol, for example, ethylene glycol.

[0028] The triol having 3-4 carbon atoms is, for example, propylene glycol.

[0029] The polyol is, for example, polyvinyl alcohol.

[0030] In some preferred embodiments of the present invention, when the alcohol water-soluble compound is selected from one or more of the monohydric primary alcohol, the dihydric alcohol having 2-8 carbon atoms, the trihydric alcohol having 3-4 carbon atoms and the polyhydric alcohol, during the irradiation process, the absorbed dose of the high-energy rays is 20-500kGy, preferably 20-400kGy, more preferably 30-300kGy, and further more preferably 50-200kGy, for example 30kGy, 80kGy, 100kGy, 150kGy or 300kGy.

[0031] In some preferred embodiments of the present invention, when the alcohol water-soluble compound is selected from the monohydric secondary alcohol and / or the monohydric tertiary alcohol, during the irradiation process, the absorbed dose of the high-energy rays is 30-400 kGy, preferably 30-300 kGy, for example 30 kGy, 100 kGy or 300 kGy.

[0032] In some preferred embodiments of the present invention, the alcohol water-soluble compound is ethanol, ethylene glycol, isopropanol, tert-butanol, ethanol and isopropanol, isopropanol and n-butanol, ethylene glycol and n-butanol, or ethylene glycol and isopropanol;

[0033] Preferably, the alcohol water-soluble compound is ethanol and isopropanol, and the mass ratio of the ethanol to the isopropanol is 1:1;

[0034] Preferably, the alcohol water-soluble compound is ethylene glycol and n-butanol, and the mass ratio of ethylene glycol to n-butanol is 2:1 or 1:1;

[0035] Preferably, the alcohol water-soluble compound is isopropanol and n-butanol, and the mass ratio of isopropanol to n-butanol is 1:2.

[0036] In the present invention, preferably, the size of the inorganic nanomaterial is 0.01-50 μm, for example, 2-50 μm.

[0037] In the present invention, preferably, when preparing the mixed solution A, the inorganic nanomaterial is first prepared as an inorganic nanomaterial dispersion.

[0038] The inorganic nanomaterial dispersion is prepared, for example, by ultrasonicating the inorganic nanomaterial in water for 1 hour.

[0039] In the present invention, the MXene two-dimensional sheet material is, for example, Ti3C2 MXene and / or Ti3C2T x MXene.

[0040] In the present invention, the metal oxide is selected from one or more of titanium dioxide, iron oxide, zinc oxide, tin oxide and zirconium dioxide. Preferably, the iron oxide is ferric oxide.

[0041] In the present invention, the metal sulfide is, for example, copper sulfide and / or cadmium sulfide.

[0042] In the present invention, preferably, in the mixed solution A, the content of the graphene oxide is 0.1-8 mg / mL, more preferably 0.5-3 mg / mL, for example 0.1 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 5 mg / mL or 10 mg / mL.

[0043] In the present invention, preferably, in the mixed solution A, the mass ratio of the graphene oxide to the monomers of acrylic acid and its derivatives is 1:(50-500), more preferably 1:(50-400), for example 1:50, 1:100, 1:200, 1:250, 1:300, 1:400 or 1:1000.

[0044] In the present invention, preferably, in the mixed solution A, the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:(0.1-50), for example, 1:0.1, 1:1, 1:5, 1:10 or 1:100.

[0045] In the present invention, preferably, in the mixed solution A, the mass percentage of the alcohol water-soluble compound in the mixed solution A is 10-50%, for example, 2%, 20%, 30% or 50%.

[0046] In the present invention, preferably, the mixed solution A is composed of graphene oxide, inorganic nanomaterials, monomers of acrylic acid and its derivatives, water and alcohol-type water-soluble compounds.

[0047] In some preferred embodiments of the present invention, in the mixed solution A, the mass ratio of the graphene oxide to the monomers of acrylic acid and its derivatives is 1:250, and during the irradiation process, the absorbed dose of the high-energy rays is 30-100 kGy.

[0048] In some preferred embodiments of the present invention, in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1, and the inorganic nanomaterial is Ti3C2MXene.

[0049] In a specific embodiment of the present invention, the preparation method of the composite hydrogel is any of the following schemes:

[0050] Scheme 1: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcoholic water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcoholic water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2MXene; the alcoholic water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy;

[0051] Scheme 2: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:0.1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2MXene; the alcohol water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy;

[0052] Scheme 3: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 10 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2MXene; the alcohol water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy;

[0053] Scheme 4: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcoholic water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 0.1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:1000, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:100; the mass percentage of the alcoholic water-soluble compound in the mixed solution A is 2%; the inorganic nanomaterial is Ti3C2 MXene; the alcoholic water-soluble compound is isopropanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 5 kGy / h, and the absorbed dose is 100 kGy;

[0054] Scheme 5: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 0.1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:1000, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:100; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 2%; the inorganic nanomaterial is CdS; the alcohol water-soluble compound is isopropanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 5 kGy / h, and the absorbed dose is 100 kGy;

[0055] Scheme 6: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 5 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:500, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 50%; the inorganic nanomaterial is CuS; the alcohol water-soluble compound is tert-butanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 300 kGy;

[0056] Scheme 7: irradiating mixed solution A with high-energy rays; wherein the mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 5 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:500, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 50%; the inorganic nanomaterial is CuS; the alcohol water-soluble compound is tert-butanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 6 kGy / h, and the absorbed dose is 300 kGy;

[0057] Scheme 8: irradiating mixed solution A with high-energy rays; wherein the mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 5 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:500, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 50%; the inorganic nanomaterial is TiO2; the alcohol water-soluble compound is tert-butanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 6 kGy / h, and the absorbed dose is 300 kGy;

[0058] Scheme 9: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 5 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:50, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 50%; the inorganic nanomaterial is TiO2; the alcohol water-soluble compound is tert-butanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 6 kGy / h, and the absorbed dose is 300 kGy;

[0059] Scheme 10: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcoholic water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 10 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcoholic water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Fe2O3; the alcoholic water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy;

[0060] Scheme 11: irradiating mixed solution A with high-energy rays; wherein the mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 10 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Fe2O3; the alcohol water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 300 kGy;

[0061] Scheme 12: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2MXene; the alcohol water-soluble compound is isopropanol and n-butanol, and the mass ratio of isopropanol to n-butanol is 1:2; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy;

[0062] Scheme 13: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:400, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 30%; the inorganic nanomaterial is TiO2; the alcohol water-soluble compound is ethylene glycol and n-butanol, and the mass ratio of ethylene glycol to n-butanol is 1:1; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 100 kGy;

[0063] Scheme 14: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:400, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 30%; the inorganic nanomaterial is CdS; the alcohol water-soluble compound is ethylene glycol and n-butanol, and the mass ratio of ethylene glycol to n-butanol is 1:1; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 100 kGy;

[0064] Scheme 15: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:100; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2 MXene; the alcohol water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy.

[0065] The present invention also provides a composite hydrogel prepared by the composite hydrogel preparation method as described above.

[0066] The present invention also provides a method for preparing a composite aerogel, which comprises the following steps: drying the composite hydrogel as described above to obtain.

[0067] In the present invention, the drying may be a conventional drying method in the art, preferably freeze drying or supercritical carbon dioxide drying.

[0068] The present invention also provides a composite aerogel prepared by the composite aerogel preparation method as described above.

[0069] In the present invention, preferably, the composite aerogel is a porous structure with a pore size distribution of 20-400 μm, such as 20-300 μm.

[0070] In the present invention, preferably, the density of the composite aerogel is 10-120 mg / cm 3 , more preferably 10-80 mg / cm 3 , for example 14.3 mg / cm 3 、16.6mg / cm 3 、25.1mg / cm 3 、33.4mg / cm 3 、33.9mg / cm 3 、37.2mg / cm 3 , 52.5mg / cm 3 、53.6mg / cm 3 、54.1mg / cm 3 、57.8mg / cm 3 、58.6mg / cm 3 、66.3mg / cm 3 、69.1mg / cm 3 、71.9mg / cm 3 or 76.8 mg / cm 3 .

[0071] The present invention also provides use of the composite hydrogel and the composite aerogel as photothermal evaporation materials.

[0072] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0073] The reagents and raw materials used in the present invention are commercially available.

[0074] The positive and progressive effects of the present invention are:

[0075] 1. The preparation method of the composite hydrogel and the preparation method of the composite aerogel of the present invention are simple to operate and environmentally friendly. The present invention directly obtains the composite hydrogel by one-step radiation reduction assembly, and further obtains the composite aerogel by drying. The radiation reduction reaction is carried out at ambient temperature, the operation is simple, and it is expected to realize the industrialization of the technology.

[0076] 2. In the preparation method of the composite hydrogel of the present invention, the raw materials of graphene oxide, inorganic nanomaterials and monomers of acrylic acid and its derivatives are from a wide range of sources and have a high utilization rate. The monomer raw materials of acrylic acid and its derivatives are completely gelled after reaction, the aqueous solution around the gel is transparent, and there is almost no loss of raw materials. A water-soluble alcohol reducing agent is selected as the irradiation reaction system, the preparation process is simple, does not involve harsh chemical reaction conditions, and avoids complex and difficult chemical reactions and purification processes.

[0077] 3. The composite aerogel of the present invention has a porous and macroporous structure with a relatively uniform structure. Its shape and size can be adjusted by using irradiation reactors of different shapes and sizes. The pore size distribution of the composite aerogel of the present invention is between 20-400 μm, the structure is relatively uniform, and the density is between 10-120 mg / cm 3 In addition, the density of the composite aerogel of the present invention can be regulated by changing the concentration of the reactants.

[0078] 4. The composite hydrogel and composite aerogel of the present invention combine the functions of graphene oxide, inorganic nanomaterials and polyacrylamide-based polymers, have excellent light absorption, heat conduction, photothermal conversion and photocatalytic properties, and also have stable water transmission and supply channels, and have excellent water supply performance; they have excellent low reflection and high light absorption capabilities in the entire solar energy spectrum, can achieve local thermal positioning, can use vertically arranged channels to efficiently transport water and significantly improve the solar-thermal energy conversion efficiency, can be used for solar light hot water evaporation and photocatalytic degradation, and have great application value in seawater desalination and wastewater purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 This is a scanning electron microscope image of the composite aerogel prepared in Example 1.

[0080] Figure 2 This is a macroscopic photograph of the composite hydrogel prepared in Example 1. DETAILED DESCRIPTION

[0081] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0082] In the embodiment of the present invention, Ti3C2 MXene powder comes from Taobao Jiacai Technology, and its flake diameter is 2-50 μm. The graphite used is provided by Sigma-Aldrich, and the graphite used is flake graphite with an average particle size of 500 μm. The remaining raw materials are provided by Sinopharm Chemical Reagent Co., Ltd.

[0083] Examples 1-15

[0084] Embodiments 1-15 respectively provide a composite aerogel. The preparation methods of Embodiments 1-15 differ in that "the type of inorganic nanomaterial in step S2", "the content of graphene oxide, the mass ratio of graphene oxide to acrylamide, the mass ratio of graphene oxide to inorganic nanomaterial, the type of alcohol water-soluble compound, and the mass percentage of alcohol water-soluble compound in the mixed solution A in step S3", and "the absorbed dose and absorbed dose rate of high-energy rays during irradiation in step S5" are different, as shown in Table 1, and the rest of the operations and conditions are the same.

[0085] The preparation method is as follows:

[0086] S1. Preparation of graphene oxide dispersion using improved oxidative exfoliation graphite method:

[0087] Add 10g of graphite, 150mL of 98% concentrated sulfuric acid, and 50mL of 65% concentrated nitric acid to a 500mL conical flask and stir at room temperature for 24h. Slowly pour into 1L of water to filter and collect the solid, wash 3 times, and dry at 80℃ for 4h. Repeat the pre-oxidation process twice. Put the dried pre-oxidized graphite into a box furnace and expand it at 900℃ for 10s to obtain thermal expansion graphite oxide. In a 500mL wide-mouth conical flask, mix 5g of thermal expansion graphite oxide with 300mL of 98% concentrated sulfuric acid, 4.2g of K2S2O8 and 6.2g of phosphorus pentoxide, heat at 80℃ for 4h, dilute with 2L of water, filter and wash, and dry in air for 3 days to obtain pre-oxidized thermal expansion graphite. 5 g of dried pre-oxidized thermal expansion graphite was mixed with 200 mL of 98% concentrated sulfuric acid at a low temperature of 0-5°C, 15 g of potassium permanganate was added slowly, stirred at 35°C for 2 h, diluted with 2 L of water and allowed to stand for 1 h, and then 20 mL of 30% hydrogen peroxide was added, allowed to stand for 2 days, the supernatant was discarded, and a mixed solution of water and ethanol in a volume ratio of 1:1 was used for centrifugal washing to obtain a solid, the solid was dispersed with water and gently stirred to obtain a well-dispersed graphene oxide dispersion, and the graphene oxide was proved to be a single layer and nanometer level by scanning electron microscopy, transmission electron microscopy and other methods;

[0088] S2, ultrasonically treating the inorganic nanomaterial in water for 1 hour to obtain an inorganic nanomaterial dispersion;

[0089] S3, mixing the graphene oxide dispersion prepared in step S1, the inorganic nanomaterial dispersion prepared in step S2, an acrylamide aqueous solution and an alcohol water-soluble compound to prepare a mixed solution A; in the mixed solution A, the content of graphene oxide, the mass ratio of graphene oxide to acrylamide, the mass ratio of graphene oxide to inorganic nanomaterial, the type of alcohol water-soluble compound, and the mass percentage of alcohol water-soluble compound in the mixed solution A are as shown in Table 1;

[0090] S4, injecting the mixed solution A obtained in step S3 into a cylindrical irradiation reactor, passing nitrogen to deoxygenate, so that there is no oxygen in the mixed solution A or the oxygen concentration is less than 5%;

[0091] S5. The sealed irradiation reactor is irradiated with a cobalt 60 gamma ray source. The absorbed dose during the irradiation process and the absorbed dose rate of the irradiation reaction are shown in Table 1. After irradiation, the composite hydrogel can be obtained.

[0092] S6. Freeze-drying the composite hydrogel obtained in step S5 to obtain a dry cylindrical composite aerogel.

[0093] Comparative Example 1

[0094] S1. The preparation method of graphene oxide dispersion is the same as that in Example 1.

[0095] S2. The preparation method of the inorganic nanomaterial dispersion is the same as that in Example 1, and the inorganic nanomaterial is Ti3C2MXene.

[0096] S3. Mix the graphene oxide dispersion prepared in step S1, the inorganic nanomaterial dispersion prepared in step S2, and the acrylamide aqueous solution to prepare a mixed solution A; in the mixed solution A, the content of graphene oxide is 1 mg / mL, the mass ratio of graphene oxide to acrylamide is 1:250, and the mass ratio of graphene oxide to inorganic nanomaterial is 1:1.

[0097] S4, injecting the mixed solution A obtained in step S3 into a cylindrical irradiation reactor and passing nitrogen gas for deoxygenation.

[0098] S5. Irradiate the sealed irradiation reactor with a cobalt-60 gamma-ray source; during the irradiation process, the absorbed dose is 30 kGy and the absorbed dose rate is 2 kGy / h.

[0099] Since no alcohol water-soluble compound is added in this comparative example, there is a lack of alcohol free radical scavengers, and the graphene oxide cannot be reduced, which greatly reduces the dispersibility of the inorganic nanomaterials, causing the inorganic nanomaterials to agglomerate, and it is impossible to obtain a uniform composite hydrogel.

[0100] The parameter conditions and irradiation conditions of the mixed solution A of Examples 1-15 and Comparative Example 1 are shown in Table 1 below.

[0101] Table 1

[0102]

[0103]

[0104] Effect Example

[0105] The photothermal evaporation rate and photocatalytic efficiency of the composite hydrogels obtained in Examples 1-15 and Comparative Example 1 were measured by solar light heating, and the water absorption swelling degree and density of the composite aerogels obtained in Examples 1-15 and Comparative Example 1 were measured.

[0106] (1) Test of water absorption and swelling

[0107] The water absorption swelling degree is tested according to conventional means in the art, and its value is obtained by the ratio of the water absorption mass to the gel mass. The formula should be: water absorption swelling degree = (mass of gel after water absorption - initial mass of gel) / initial mass of gel, measured at room temperature, and water is absorbed to saturation.

[0108] (2) Testing of water evaporation performance by solar heating

[0109] The performance of solar-heated water evaporation is evaluated by measuring the photothermal evaporation rate during solar heating. The photothermal evaporation rate is obtained by the ratio of the mass of water evaporated by solar heating to the surface area of ​​the gel and the evaporation time, that is, the formula is: photothermal evaporation rate = mass of water evaporated after solar heating / (surface area of ​​the gel*evaporation time).

[0110] The present invention takes the evaporation of deionized water as an example. 2 , measured at a temperature of 25°C and a humidity of 50%.

[0111] (3) Test of photocatalytic efficiency

[0112] The photocatalytic performance was tested according to conventional means in the field, and its value was obtained by the ratio of the concentration after catalytic degradation to the original concentration, that is, photocatalytic efficiency = concentration after catalytic degradation / original concentration.

[0113] Taking the photocatalytic degradation of methylene blue as an example, the original concentration is 10 mg / mL. At room temperature, based on a catalyst content of 10 mg, 50 mL of methylene blue was catalyzed for 3 hours.

[0114] (4) Test of composite aerogel density

[0115] The mass of the composite aerogel divided by its volume is the density of the composite aerogel.

[0116] (5) Temperature change test

[0117] The temperature change of the composite hydrogel evaporator surface during the evaporation process is detected by an infrared temperature detector, including the initial temperature before evaporation and the final temperature after evaporation.

[0118] The photothermal evaporation rate and photocatalytic efficiency of the composite hydrogels obtained in Examples 1-15 and Comparative Example 1 by solar light heating, and the water absorption swelling degree, density and pore size distribution results of the composite aerogels obtained in Examples 1-15 and Comparative Example 1 are shown in Table 2.

[0119] Table 2

[0120]

[0121]

[0122] Figure 1 This is a scanning electron microscope photograph of the composite aerogel prepared in Example 1, wherein the detection conditions are a voltage of 15.00 kV and a magnification of 500X. Figure 2 The macroscopic photograph of the composite hydrogel prepared in Example 1. The composite hydrogels prepared in Examples 2-15 are similar to those in Example 1.

[0123] As shown in Table 2, the composite hydrogels prepared in Examples 1-15 not only have good light-to-heat conversion performance, but also have a surface temperature range of 19-31°C and an evaporation rate of 3.037-4.672 kg·m under the irradiation of one sun. -2 ·h -1 The photocatalytic degradation efficiency is between 84% and 99%. The composite aerogel obtained after drying also has excellent water absorption performance, and the water absorption swelling degree is between 7.24 and 17.62 g·g -1 The density of composite aerogel is also low, ranging from 14.3 to 76.8 mg / cm 3 between.

[0124] It can be seen from Examples 10-11 that when the content of graphene oxide, the mass ratio of graphene oxide to acrylamide, the mass ratio of graphene oxide to inorganic nanomaterials, the type of alcohol water-soluble compounds, the mass percentage of alcohol water-soluble compounds in the mixed solution A, and the absorbed dose rate of the irradiation reaction are all the same in the mixed solution A, the photothermal evaporation rate and photocatalytic efficiency of the composite hydrogel obtained when the irradiation absorbed dose is between 30 and 300 kGy are better, and the water absorption swelling degree and density of the composite aerogel are better.

[0125] It can be seen from Examples 1-2 and Example 15 that as the content of inorganic nanomaterials increases, the photothermal evaporation rate and photocatalytic efficiency of the obtained composite hydrogel increase, and the water absorption swelling degree and density of the obtained composite aerogel also increase.

[0126] It can be seen from Examples 8-9 that with the increase of the monomer content of acrylic acid and its derivatives, the photothermal evaporation rate of the obtained composite hydrogel increases, the photocatalytic efficiency of the obtained composite hydrogel decreases, and the water absorption swelling degree and density of the obtained composite aerogel also increase.

[0127] In addition, it can be seen from Examples 6-7 that the water absorption swelling degree increases with the increase of irradiation and absorbed dose rate, and it can be seen from Examples 10-11 that the water absorption swelling degree decreases with the increase of irradiation.

[0128] It can be seen from Examples 1 and 3 that when the mass ratio of graphene oxide to inorganic nanomaterials and the mass ratio of graphene oxide to acrylamide in mixed solution A are the same, when the concentration of graphene oxide in mixed solution A is between 0.1-10 mg / mL, the photothermal evaporation rate and photocatalytic degradation effect of the prepared composite hydrogel are both good, and the water absorption and swelling degree of the composite aerogel is also good. When the concentration of graphene oxide is between 0.1-10 mg / mL, the water absorption and swelling degree of the composite aerogel will significantly increase as the concentration of graphene oxide decreases, and the photothermal evaporation rate of the composite hydrogel will increase as the concentration of graphene oxide increases.

[0129] It can be seen from Examples 1-2 and 15 that when the mass ratio of graphene oxide to inorganic nanomaterials is between 1:(0.1-100), the water absorption swelling degree of the composite aerogel, the photothermal evaporation rate of the composite hydrogel and the photocatalytic degradation effect are all good. When the mass ratio of graphene oxide to inorganic nanomaterials is between 1:(0.1-100), the water absorption swelling degree of the composite aerogel will increase significantly with the increase of the content of inorganic nanomaterials, and the photothermal evaporation rate and photocatalytic degradation efficiency of the composite hydrogel will increase with the increase of the content of inorganic nanomaterials.

[0130] It can be seen from Example 1 and Example 12 that when the content of the alcohol water-soluble compound, the absorbed dose and the absorbed dose rate of the irradiation reaction are the same, two alcohol water-soluble compounds are selected as reducing agents, and the prepared composite hydrogel has a higher photothermal evaporation rate, and the addition of isopropanol and n-butanol can also significantly improve the water absorption and swelling degree of the composite aerogel.

[0131] It can be seen from Examples 4 and 5, 7 and 8, 3 and 10, and 13 and 14 that the photothermal evaporation rate and photocatalytic degradation efficiency of the composite hydrogel are affected by the type of inorganic nanomaterials.

[0132] In Comparative Example 1, since no alcohol water-soluble compound is added as a reducing agent, the degree of reduction of graphene oxide is greatly reduced, the dispersibility of MXene is greatly reduced, the elasticity of the obtained hydrogel deteriorates, and it cannot float in water. The photothermal conversion performance, photocatalytic performance, water absorption and swelling capacity and evaporation rate are all much lower than those of Examples 1-15.

[0133] As can be seen from the above, the mass percentage of alcohol water-soluble compounds in the mixed solution A is 2-50%, the mass ratio of graphene oxide to monomers of acrylic acid and its derivatives is 1:(50-1000), the mass ratio of graphene oxide to inorganic nanomaterials is 1:(0.1-100), the content of graphene oxide in the mixed solution A is 0.1-10 mg / mL, and during the irradiation process, when the absorbed dose is 30-300 kGy, the prepared composite hydrogel has a large evaporation rate and photocatalytic degradation efficiency, and the composite aerogel has excellent water absorption and swelling degree.

[0134] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite hydrogel, characterized in that: It includes the following steps: High-energy rays irradiate mixed solution A; wherein the mixed solution A comprises graphene oxide, inorganic nanomaterials, monomers of acrylic acid and its derivatives, water and alcohol-type water-soluble compounds; the inorganic nanomaterials are selected from one or more of MXene two-dimensional sheet materials, metal oxides and metal sulfides; In the mixed solution A, the content of the graphene oxide is 0.05-10 mg / mL, the mass ratio of the graphene oxide to the monomers of acrylic acid and its derivatives is 1:(50-1000), and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:(0.1-100); the mass percentage of the alcohol water-soluble compound in the mixed solution A is 2-50%.

2. The method for preparing the composite hydrogel according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The high-energy rays are cobalt-60 gamma rays or electron beam rays; (2) The irradiation is carried out in an irradiation reactor, and the irradiation reactor is, for example, a cylindrical irradiation reactor; (3) During the irradiation process, the absorbed dose rate of the high energy rays is 0.1-10 kGy / h, for example, 2 kGy / h, 5 kGy / h or 6 kGy / h; (4) During the irradiation process, the absorbed dose of the high-energy rays is 20-500 kGy, preferably 20-400 kGy, more preferably 30-300 kGy, and further more preferably 50-200 kGy, for example, 30 kGy, 80 kGy, 100 kGy, 150 kGy or 300 kGy; (5) before irradiating the mixed liquid A with high-energy rays, introducing nitrogen and / or argon into the mixed liquid A; (6) The mixed solution A is free of oxygen or has an oxygen concentration lower than 5%; (7) The size of the graphene oxide is nanoscale graphene oxide; (8) When preparing the mixed solution A, the graphene oxide is first prepared as a graphene oxide dispersion; wherein the solvent of the graphene oxide dispersion is preferably water; (9) The monomer of acrylic acid and its derivatives is selected from one or more of acrylamide, acrylic acid, methacrylic acid, and N,N-dimethylacrylamide, such as acrylamide; (10) The alcohol water-soluble compound is selected from one or more of a monohydric alcohol having 1 to 4 carbon atoms, a dihydric alcohol having 2 to 8 carbon atoms, a trihydric alcohol having 3 to 4 carbon atoms, and a polyhydric alcohol; Preferably, the monohydric alcohol having 1 to 4 carbon atoms is selected from one or more of a primary monohydric alcohol, a secondary monohydric alcohol and a tertiary monohydric alcohol; More preferably, the monohydric primary alcohol is selected from one or more of methanol, ethanol, n-propanol and n-butanol, for example, ethanol; More preferably, the monohydric secondary alcohol is isopropanol and / or isobutanol, for example, isopropanol; More preferably, the monohydric tertiary alcohol is tert-butyl alcohol; Preferably, the diol having 2 to 8 carbon atoms is selected from one or more of ethylene glycol, propylene glycol and octanediol, for example, ethylene glycol; Wherein, the triol having 3-4 carbon atoms is, for example, propylene glycol; Wherein, the polyol is, for example, polyvinyl alcohol; (11) The size of the inorganic nanomaterial is 0.01-50 μm, for example, 2-50 μm; (12) When preparing the mixed solution A, first prepare the inorganic nanomaterial into an inorganic nanomaterial dispersion; Wherein, the inorganic nanomaterial dispersion is prepared, for example, by ultrasonicating the inorganic nanomaterial in water for 1 hour; (13) The MXene two-dimensional sheet material is Ti3C2 MXene and / or Ti3C2T x MXene; (14) The metal oxide is selected from one or more of titanium dioxide, iron oxide, zinc oxide, tin oxide and zirconium dioxide. Preferably, the iron oxide is ferric oxide; (15) The metal sulfide is copper sulfide and / or cadmium sulfide; (16) In the mixed solution A, the content of the graphene oxide is 0.1-8 mg / mL, more preferably 0.5-3 mg / mL, for example 0.1 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 5 mg / mL or 10 mg / mL; (17) In the mixed solution A, the mass ratio of the graphene oxide to the monomers of acrylic acid and its derivatives is 1:(50-500), preferably 1:(50-400), for example, 1:50, 1:100, 1:200, 1:250, 1:300, 1:400 or 1:1000; Preferably, in the mixed solution A, the mass ratio of the graphene oxide to the monomers of acrylic acid and its derivatives is 1:250, and during the irradiation process, the absorbed dose of the high-energy rays is 30-100 kGy; (18) In the mixed solution A, the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:(0.1-50), for example, 1:0.1, 1:1, 1:5, 1:10 or 1:100; (19) In the mixed solution A, the alcohol water-soluble compound accounts for 10-50% by mass of the mixed solution A, for example, 2%, 20%, 30% or 50%; (20) The mixed solution A is composed of graphene oxide, inorganic nanomaterials, monomers of acrylic acid and its derivatives, water and alcohol-based water-soluble compounds.

3. The method for preparing the composite hydrogel according to claim 2, characterized in that: It meets one or more of the following conditions: (1) In the mixed solution A, the content of graphene oxide is 1 mg / mL; (2) In the mixed solution A, the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; (3) In the mixed solution A, the inorganic nanomaterial is Ti3C2 MXene; (4) When the alcohol water-soluble compound is selected from one or more of the monohydric primary alcohol, the dihydric alcohol having 2 to 8 carbon atoms, the trihydric alcohol having 3 to 4 carbon atoms and the polyhydric alcohol, the absorbed dose of the high-energy rays during the irradiation process is 20 to 500 kGy, preferably 20 to 400 kGy, more preferably 30 to 300 kGy, and further more preferably 50 to 200 kGy, for example, 30 kGy, 80 kGy, 100 kGy, 150 kGy or 300 kGy; Or, when the alcohol water-soluble compound is selected from the monohydric secondary alcohol and / or the monohydric tertiary alcohol, during the irradiation process, the absorbed dose of the high-energy rays is 30-400 kGy, preferably 30-300 kGy, for example, 30 kGy, 100 kGy or 300 kGy; (5) The alcohol water-soluble compound is ethanol, ethylene glycol, isopropanol, tert-butanol, ethanol and isopropanol, isopropanol and n-butanol, ethylene glycol and n-butanol, or ethylene glycol and isopropanol; Preferably, the alcohol water-soluble compound is ethanol and isopropanol, and the mass ratio of the ethanol to the isopropanol is 1:1; Preferably, the alcohol water-soluble compound is ethylene glycol and n-butanol, and the mass ratio of ethylene glycol to n-butanol is 2:1 or 1:1; Preferably, the alcohol water-soluble compound is isopropanol and n-butanol, and the mass ratio of isopropanol to n-butanol is 1:

2.

4. The method for preparing the composite hydrogel according to claim 1, characterized in that: The preparation method of the composite hydrogel is any of the following schemes: Scheme 1: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcoholic water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcoholic water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2MXene; the alcoholic water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy; Scheme 2: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:0.1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2MXene; the alcohol water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy; Scheme 3: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 10 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2MXene; the alcohol water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy; Scheme 4: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcoholic water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 0.1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:1000, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:100; the mass percentage of the alcoholic water-soluble compound in the mixed solution A is 2%; the inorganic nanomaterial is Ti3C2 MXene; the alcoholic water-soluble compound is isopropanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 5 kGy / h, and the absorbed dose is 100 kGy; Scheme 5: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 0.1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:1000, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:100; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 2%; the inorganic nanomaterial is CdS; the alcohol water-soluble compound is isopropanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 5 kGy / h, and the absorbed dose is 100 kGy; Scheme 6: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 5 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:500, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 50%; the inorganic nanomaterial is CuS; the alcohol water-soluble compound is tert-butanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 300 kGy; Scheme 7: irradiating mixed solution A with high-energy rays; wherein the mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 5 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:500, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 50%; the inorganic nanomaterial is CuS; the alcohol water-soluble compound is tert-butanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 6 kGy / h, and the absorbed dose is 300 kGy; Scheme 8: irradiating mixed solution A with high-energy rays; wherein the mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 5 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:500, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 50%; the inorganic nanomaterial is TiO2; the alcohol water-soluble compound is tert-butanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 6 kGy / h, and the absorbed dose is 300 kGy; Scheme 9: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 5 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:50, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 50%; the inorganic nanomaterial is TiO2; the alcohol water-soluble compound is tert-butanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 6 kGy / h, and the absorbed dose is 300 kGy; Scheme 10: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcoholic water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 10 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcoholic water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Fe2O3; the alcoholic water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy; Scheme 11: irradiating mixed solution A with high-energy rays; wherein the mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 10 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Fe2O3; the alcohol water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 300 kGy; Scheme 12: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2MXene; the alcohol water-soluble compound is isopropanol and n-butanol, and the mass ratio of isopropanol to n-butanol is 1:2; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy; Scheme 13: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:400, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 30%; the inorganic nanomaterial is TiO2; the alcohol water-soluble compound is ethylene glycol and n-butanol, and the mass ratio of ethylene glycol to n-butanol is 1:1; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 100 kGy; Scheme 14: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:400, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:1; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 30%; the inorganic nanomaterial is CdS; the alcohol water-soluble compound is ethylene glycol and n-butanol, and the mass ratio of ethylene glycol to n-butanol is 1:1; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 100 kGy; Scheme 15: irradiating mixed solution A with high-energy rays; wherein mixed solution A comprises graphene oxide, inorganic nanomaterials, acrylamide, water and alcohol water-soluble compounds; in the mixed solution A, the content of the graphene oxide is 1 mg / mL, the mass ratio of the graphene oxide to the acrylamide is 1:250, and the mass ratio of the graphene oxide to the inorganic nanomaterial is 1:100; the mass percentage of the alcohol water-soluble compound in the mixed solution A is 20%; the inorganic nanomaterial is Ti3C2 MXene; the alcohol water-soluble compound is ethanol; the high-energy ray is cobalt 60 gamma ray, and during the irradiation process, the absorbed dose rate of the high-energy ray is 2 kGy / h, and the absorbed dose is 30 kGy.

5. A composite hydrogel, characterized in that: The composite hydrogel is prepared by the method for preparing the composite hydrogel according to any one of claims 1 to 4.

6. A method for preparing a composite aerogel, characterized in that: The composite hydrogel as claimed in claim 5 is dried to obtain the obtained product.

7. The method for preparing the composite aerogel according to claim 6, characterized in that: The drying is freeze drying or supercritical carbon dioxide drying.

8. A composite aerogel, characterized in that: The composite hydrogel is prepared by the method for preparing the composite aerogel according to claim 6 or claim 7.

9. The composite aerogel according to claim 8, characterized in that The composite aerogel has a porous structure, and the pore size distribution is 20-400 μm, for example, 20-300 μm; And / or, the density of the composite aerogel is 10-120 mg / cm 3 , more preferably 10-80 mg / cm 3 , for example 14.3 mg / cm 3 、16.6mg / cm 3 、25.1mg / cm 3 、33.4mg / cm 3 、33.9mg / cm 3 、37.2mg / cm 3 , 52.5mg / cm 3 、53.6mg / cm 3 、54.1mg / cm 3 , 57.8mg / cm 3 、58.6mg / cm 3 、66.3mg / cm 3 、69.1mg / cm 3 、71.9mg / cm 3 or 76.8 mg / cm 3 .

10. Use of the composite hydrogel according to claim 5 and the composite aerogel according to claim 8 or claim 9 as photothermal evaporation materials.

Citation Information

Cited By

  • Biomass photo-thermal interface evaporation material based on Cu-Zn-S photo-thermal catalytic layer as well as preparation method and application of biomass photo-thermal interface evaporation material

    CN120987411A